EFFECTS OF HUMIC ACID AND BREAD YEAST ON GROWTH AND YIELD OF LETTUCE (LACTUCA SATIVA L.) UNDER PROTECTED CONDITIONS - IBRAHIM, IBRAHIM RAJAB (Journal of Duhok University, 2020)
A research study was conducted in a plastic house (500m2 ) at the vegetable research field of the protected cultivated department at Zakho Technical Institute, Dohuk Polytechnic University, Kurdistan Region-Iraq. The period of study was at Autumn season of 2018 to investigate the effect of foliar application of humic acid in three levels (0, 2 and 4) ml/L and bread yeast with three levels (0, 2.5 and 5) g/L on the growth and yield of lettuce (Cv. Romaine). The results showed that treatment with foliar spraying of humic acid and yeast had significant effects on growth and yield of letteus , The level (4) ml/L , also the foliar spraying of yeast at the level (5) g/L had the highest results in the growth of vegetative characters ( No. of leaves. plant-1 76.41leaves and chlorophyll content% 45.04%), leaf mineral content (Nitrogen, Potassium and Phosphorus) and head weight (gm) of lettuce when encountered with control and other treatments.